2020
DOI: 10.1186/s12985-020-1281-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of HIV-1 epidemic in Anhui Province, China

Abstract: Background: Anhui Province in China is facing a severe HIV epidemic with an increasing number of newly diagnosed cases. Methods: In this study, HIV genetic characteristics in the province were investigated. Newly reported HIV-positive individuals from 15 districts of Anhui Province were enrolled and interviewed. Total viral RNA was extracted from plasma isolated from blood samples. We amplified and sequenced an HIV pol fragment of the 1062 bp. The sequences were used for determination of HIV subtypes and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…The predominant CRFs in our study were similar to other provinces in China 26 , 35 , 36 , but different from those in southeast Asian countries 31 33 , United States 29 , Canada and European countries 37 41 . The newly detected CRFs in our study had been circulating in the northeast and middle and southern parts of China since 2013 42 – 46 , which concurred with the results from our temporal geographical analysis.…”
Section: Discussionsupporting
confidence: 91%
“…The predominant CRFs in our study were similar to other provinces in China 26 , 35 , 36 , but different from those in southeast Asian countries 31 33 , United States 29 , Canada and European countries 37 41 . The newly detected CRFs in our study had been circulating in the northeast and middle and southern parts of China since 2013 42 – 46 , which concurred with the results from our temporal geographical analysis.…”
Section: Discussionsupporting
confidence: 91%
“…The genetic distance cut-off value for constructing the transmission network differs among sequences belonging to different subtypes. 34 In the present study, genetic distances ≤0.013 and ≤0.015 were set as cut-off values for CRF07_BC and CRF01_AE, CRF55_01B, or CRF59_01B, respectively. The results showed that most (70.4% for CRF01_AE, 63.6% for CRF07_BC, and 55.8% for CRF55_01B) of the MSM in transmission networks were concentrated at ages below 35 years old.…”
Section: Discussionmentioning
confidence: 99%
“…RIP and jpHMM tools in HIV database were used to identify the recombinant strains. 11 A phylogenetic tree was constructed by the neighborjoining method based on the Kimura 2-parameter model with 10 0 0 bootstrap replicates in MEGA6 software to determine the subtypes of the sequences. 12…”
Section: Hiv-1 Subtypingmentioning
confidence: 99%